Appraisal Theory and Interpreting Political Speech - Alhuthali, Mohammed (European Scientific Journal, ESJ, 2024)
Appraisal theory can be used to study the semiotic content of formal speeches. This paper focuses on the study of two speeches by Ban Ki Moon. The first in 2006 was his acceptance speech and the second, in 2016, was his speech on leaving his role as Secretary General of the United Nations. By employing the same speaker and organization, this helps remove variances due to personal or corporate style. It also allows a focus on how different semiotic approaches are used at different stages of each speech. While affect is common across the speech structure, judgement is more commonly found in sections that can be seen as instances of expected politeness towards the intended audience. By using such modes, the speaker is effectively inviting agreement with their overall presentation. This also suggests a linkage between chosen mode and purpose. However, meaning-making cannot just be understood through a sentence by sentence analysis and there still remains a need to take a holistic overview and place the speech in a wider context.